Tusaaji Tusilaartuq: When the Translator Must be Hard of Hearing - Dorais, Louis-Jacques (Tusaaji: A Translation Review, 2016)
This article examines how translation to and from Inuktitut, the language of the Eastern Canadian Inuit, often compels the translator to create new words or explanatory phrases in the target language, in order to cope with the existing cultural and semantic gaps between most Indigenous languages and languages of wider communication. Moreover, the transcription of Inuktitut into the syllabic script also entails phonetic distortions. The article concludes that some types of translations in Inuktitut are practically useless, but that more Inuktitut oral and written texts should be translated into mainstream languages.